2008
DOI: 10.3758/mc.36.5.1033
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements and parafoveal word processing in reading Chinese

Abstract: In two experiments, a parafoveal lexicality effect in the reading of Chinese (a script that does not physically mark word boundaries) was examined. Both experiments used the boundary paradigm (Rayner, 1975) and indicated that the lexical properties of parafoveal words influenced eye movements. In Experiment 1, the preview stimulus was either a real word or a pseudoword. Targets with word previews, even unrelated ones, were more likely to be skipped than were those with pseudowords. In Experiment 2, all of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 42 publications
5
54
0
Order By: Relevance
“…In these cases, it is unclear exactly what information contributed to the decision to skip the word: The skipping decision could have been a result of actual semantic processing or of orthographic information simply confirming one of a constrained set of lexical candidates. The latter idea fits in well with the finding that readers are more likely to skip words (as compared with nonwords; Blanchard et al, 1989;White, Warren, & Reichle, 2011;Yen, Tsai, Tzeng, & Hung, 2008), suggesting that lexical status contributes to the decision to skip a word. Additionally, skipping, especially of short words, can also be caused by simple oculomotor error resulting in mislocated fixations .…”
Section: Skipping Effectssupporting
confidence: 70%
See 1 more Smart Citation
“…In these cases, it is unclear exactly what information contributed to the decision to skip the word: The skipping decision could have been a result of actual semantic processing or of orthographic information simply confirming one of a constrained set of lexical candidates. The latter idea fits in well with the finding that readers are more likely to skip words (as compared with nonwords; Blanchard et al, 1989;White, Warren, & Reichle, 2011;Yen, Tsai, Tzeng, & Hung, 2008), suggesting that lexical status contributes to the decision to skip a word. Additionally, skipping, especially of short words, can also be caused by simple oculomotor error resulting in mislocated fixations .…”
Section: Skipping Effectssupporting
confidence: 70%
“…In Chinese, the morpheme that a character represents can differ, depending on the word in which it is embedded. Yen et al (2008) found that preview benefits were larger when the preview and target shared a character that represented the same morpheme, as compared with a condition in which the character was the same (orthographically) but the morpheme it represented differed between the preview word and the target word. Recently, Yang (2010) reported a preview benefit for twocharacter (i.e., bimorphemic) Chinese compound words.…”
Section: Morphological Processingmentioning
confidence: 89%
“…The present result of semantic activation from parafoveally presented Korean words extends our knowledge on parafoveal high-level information processing. There is considerable additional evidence for parafoveal (morpho-)semantic processing in Chinese (Yan, Pan, Bélanger, & Shu, 2015;Yan & Sommer, 2015;Yen, Tsai, Tzeng, & Hung, 2008). In contrast, such effects appear to be limited to synonym previews in English (Schotter, 2013) or to scripts with relatively transparent letter-phoneme correspondence, such as German (Hohenstein, Laubrock, & Kliegl, 2010;Hohenstein & Kliegl, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Yen et al (2008) have shown that a word can be activated from the parafovea (also see Yang et al, 2009). However, only character-level information can be obtained from the remaining area (e.g., C3) farther in the parafovea.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that both character-and word-level information of the fixated stimulus can be extracted during fixation and influence eye movements. Second, a parafoveal lexicality effect has been observed (Yang, Wang, Xu, & Rayner, 2009;Yen, Tsai, Tzeng, & Hung, 2008). Masking the parafoveal word (the target) with a pseudoword consisting of real characters lengthened the subsequent target viewing durations.…”
Section: Eye Movements In Reading Chinesementioning
confidence: 97%